Penerapan PSAK 72: Pengaruh Pendapatan Usaha dan Biaya Operasional terhadap Laba Bersih pada Perusahaan di Industri Real Estate dan Properti dan Properti yang Terdaftar di Bursa Efek Indonesia Tahun 2017 – 2022 - Suryono Endrojoyo; Vinola Herawaty (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The real estate and property sector plays a pivotal role in driving economic growth which similar to other industries, real estate and property companies engage in business activities to generate revenue by utilizing their resources, including operational expenses, with the ultimate goal of achieving profitability. This study aims to analyze the effect of revenue and operating expenses before and after the implementation of PSAK 72 concerning Income from Contracts with Customers on net profit in real estate and property companies listed on the Indonesia Stock Exchange (IDX). This research uses a quantitative method with secondary data. The population of this research is 91 companies and the research sample is 56 samples based on the availability of financial reports for the 2017-2022 period on the BEI website https://www.idx.co.id/id and the respective company websites. Data analysis was conducted is using panel data regression with classical tests and multiple linear regression as the analysis techniques. The program used to process the data is EViews 12. The results of the study show that revenue and operating expenses have a partial effect on net profit, and revenue and operating expenses have a significant effect on net profit of 66.48%.